Biological responses of an elite centipedegrass [Eremochloa ophiuroides (Munro) Hack.] cultivar (Ganbei) to carbon ion beam irradiation - Zhang, Yuan; Wang, Haoran; Du, Yan; Zhang, Ling; Li, Xiaohui; Guo, Hailin; Liu, Jianxiu; Zhou, Libin; Xu, Xin; Li, Jianjian (Frontiers in Plant Science, 2024)
Carbon ion beam irradiation (CIBI) is a highly efficient mutagenesis for generating mutations that can be used to expand germplasm resources and create superior new germplasm. The study investigated the effects of different doses of CIBI (50 Gy, 100 Gy, 150 Gy, 200 Gy and 300 Gy) on seed germination and seedling survival, seedling morphological and physiological traits of an elite centipedegrass cultivar Ganbei. The results showed that irradiation greater than 50 Gy cause inhibition of seed germination, and the semi-lethal dose (LD50) is around 90 Gy for CIBI treated seeds of Ganbei. A carbon ion beam-mutagenized centipedegrass population was generated from Ganbei, with irradiation dosages from 50 Gy to 200 Gy. More than ten types of phenotypic variations and novel mutants with heritable tendencies mainly including putative mutants of stolon number, length and diameter, of internode length, of leaf length and width, of leaf chlorophyll content, of stolon growth rate, of aboveground tissue dry weight, of sward height were identified.While the total sugar content of the plants from irradiated seeds showed no obvious change in all treatments as compared to the control, the crude protein content displayed significant reduction at a